Government health expenditures and health outcome nexus: a study on OECD countries - Anwar, Asim; Hyder, Shabir; Mohamed Nor, Norashidah; Younis, Mustafa (Frontiers in Public Health, 2023)
Introduction: The consistent increase in health expenditures is an integral part of health policy. The aim of this study was to investigate the impact of health expenditures on health outcomes in the OECD countries. Method: We used the system generalized method of moments (GMM) for thirty eight OECD countries using panel data from 1996 to 2020. Results and discussion: The findings show that health expenditures have a negative impact on infant mortality while positive on life expectancy. The results further verify that the income measured as GDP, number of doctors, and air pollution has a negative effect on infant mortality, while these variables have a positive effect on life expectancy in the studied countries. The outcome of the study suggests that health expenditures need to be properly utilized and improvements can be made in the health policies to increase the investment in health technology. The government should also focus on measures like economic and environmental to have long-lasting health outcomes.